Modular robots + synchronous robots + multi-arm robots - Buckingham, Rob (Industrial robot ;, 2003)
As soon as trade progresses beyond swappingchickens for grain at your local market youneed standards. This includes standardweights and measures, currency andspecifications for quality and operatingperformance. Our whole engineering world revolvesaround precise measurements of time, distance and mass.